2018
DOI: 10.3390/geriatrics3030044
|View full text |Cite
|
Sign up to set email alerts
|

Use of Clinical Video Telehealth as a Tool for Optimizing Medications for Rural Older Veterans with Dementia

Abstract: Community-Based Outpatient Clinics (CBOCs) allow delivery of primary care to rural veterans who are far from a main Veterans Affairs (VA) campus. However, CBOCs often do not have physicians with geriatric training. We used a clinical video telehealth (CVT) dementia service (Teledementia clinic) based in the Pittsburgh VA Healthcare System to optimize dementia patients' medications and potentially inappropriate medications (PIMs). We analyzed 199 CVT patient encounters from 1 January 2016 to 31 December 2016 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…The mean age of reported participants was 78.6 years. Three studies were conducted in an exclusive male veterans population [ 14 , 16 , 19 ]. The median study time for the interventions was 12 months (range 5–48 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of reported participants was 78.6 years. Three studies were conducted in an exclusive male veterans population [ 14 , 16 , 19 ]. The median study time for the interventions was 12 months (range 5–48 months.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the nine studies reported on clinical benefit outcomes ( Table 4 ) [ 12 , 14 , 16–18 , 20 ]. Four studies reported successful medication rationalization [ 14 , 16–18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GeriPACTs employ a range of staffing and clinical structures that are adapted to local needs. Clinical video telehealth (CVT) is also being employed by the VA to improve access for rural residents [ 5 ] and for consultative services, including dementia care and caregiver support [ 6 ]. Telehealth appears to be well accepted by patients and effective in optimizing geriatric care and obtaining community-based long-term care services and support (LTSS).…”
mentioning
confidence: 99%
“…Outcomes from consultations. Medication changes have been reported as an outcome of geriatric assessment through telehealth (Conn, Madan, Lam, Patterson, & Skirten, 2013), but compared to initial assessment, follow-up assessments through videoconferencing result in fewer medication changes (Chang, Homer, & Rossi, 2018). Chang et al (2018) reported that potentially innapropriate medications were recognized and discontinued more often during initial assessments so that subsequent consultations resulted in fewer medication changes.…”
Section: Telegeriatrics Findingsmentioning
confidence: 99%